Contextual Learning of Islamic Religious Education in the Wasiat “Ingsun Titip Tajug Lan Fakir Miskin” - Achmad Muhajir; Eddy Saputra (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2025)
Sunan Gunung Jati is an important figure in the spread of Islam in the Cirebon region, a city and district at the northern tip of West Java. There are messages left to be studied and put into practice in the context of Islamic religious education. This article discusses the meaning and implementation of Sunan Gunung Jati's